Anatomy of a Public-Private Partnership: Hold-up and regulatory risk in an NGN PPP - Bronwyn Howell; Bert Sadowski (International Telecommunications Society (ITS), 2014)
In recent years, the preference for purely private funding and ownership of telecommunications networks has given way to a 'new wisdom' that some form of public funding is now necessary if faster and more capacious Next Generation Networks (NGNs) are to be constructed in a timely fashion. The relevant question for policymakers is how that public investment will take place. The preferred approach in most cases appears to be to by way of Public-Private Partnerships (PPPs) where public and private actors collaborate in NGN investment, construction and operation. However, the body of analysis of NGN PPPs to guide policy-makers is scant. This paper addresses the gap by applying the learnings from classic, more mature PPPs (e.g. roading) and applying them to the NGN context. We use a case study of New Zealand's Ultrafast Broadband Initiative PPPs - one of the first nationwide partnerships undertaken - to illustrate the relevance of the insights. We find that NGN PPPs reverse the typical direction of financing and ownership observed in roading PPPs. The bundling of design, financing construction and operation of classic PPPs is 'undone' in NGN PPPs, as financing and asset ownership are separated, increasing the potential for misalignment of incentives and the likelihood that the public party can hold up the private party once existing network assets are sunk in the partnership by altering regulatory settings. Whilst the government instigating the PPP may not be inclined to act opportunistically, a successive government facing different political priorities does not face the same incentives. To the extent that the private party can anticipate this risk, it should endeavour to include terms in the initial agreement ensuring that the public party is penalised if such an event occurs (i.e. an automatic right to favourable renegotiation or payment of compensation) so that such opportunism is discouraged and the project benefits from time-consistent alignment of incentives and objectives. Had such provisions been in place in the New Zealand PPPs, costly consequences of regulatory change threatening the completion of the NGN would have been avoided.
Keywords: 330